2016
DOI: 10.1093/eurheartj/ehw250
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs strongly predict cardiovascular death in patients with coronary artery disease—results from the large AtheroGene study

Abstract: This is the largest study so far evaluating the prognostic value of circulating miRNAs in cardiovascular disease. Our study shows that single miRNAs derived from peripheral blood predict mortality in secondary prevention settings, and thereby represent valuable biomarkers for risk estimation in CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 20 publications
0
118
0
Order By: Relevance
“…Matrix vesicles contribute to calcification by carrying and depositing calcium crystals [33]. MicroRNAs are roughly 22 nucleotides long, singlestranded molecules that function to regulate gene expression by binding to mRNA, usually in the 3'UTR, to decrease mRNA translation and stability [34], microRNAs have also been found to play an important role in cardiovascular diseases [35][36][37][38][39]. We have found high enrichment of microRNAs after 20 days of Lp (a) treatment in HAVICs.…”
Section: Discussionmentioning
confidence: 95%
“…Matrix vesicles contribute to calcification by carrying and depositing calcium crystals [33]. MicroRNAs are roughly 22 nucleotides long, singlestranded molecules that function to regulate gene expression by binding to mRNA, usually in the 3'UTR, to decrease mRNA translation and stability [34], microRNAs have also been found to play an important role in cardiovascular diseases [35][36][37][38][39]. We have found high enrichment of microRNAs after 20 days of Lp (a) treatment in HAVICs.…”
Section: Discussionmentioning
confidence: 95%
“…Latest results with respect to prognostic miRNA evaluation in MI report a set of five miRNAs associated with future MI in the HUNT study [32], while a set of seven miRNAs was identified to reliably predict cardiovascular death in patients with CAD in the AtheroGene study [30]. The first data from a large-scale study were reported by Zampetaki et al in 2012 [97].…”
Section: Mirnas In Prediction and Prognosis Of Coronary Artery Diseasmentioning
confidence: 99%
“…Additionally, since UAP is atherosclerosis without substantial ischemia, some overlap with previously found markers for SAP in earlier studies would have been expected. However, none of the eight microRNAs that were measured in the study of Karakas et al (4) were found in a total of 17 earlier studies on SAP markers (12). Although, the study of Zeller et al (5) is the first to consistently show an association of microRNAs with UAP in three independent cohorts, we maintain to wonder why so many different study of microRNA biomarkers produce different results.…”
Section: Relation To Other Micrornas Studiesmentioning
confidence: 90%